Secret pills: HIV-positive patients' experiences taking antiretroviral therapy in North Carolina - Golin, C.; Isasi, F.; Bontempi, J.B.; Eng, E. (AIDS Education and Prevention, 2002)
Understanding the barriers to antiretroviral adherence is a critical step in improving the effectiveness of HIV treatment and saving lives. We sought to assess, qualitatively, the experiences of HIV-positive persons taking antiretroviral therapy (ART) in North Carolina. Twenty-four people participated in one of six focus groups. A structured interview script included three questions (two open-ended) and eight probes. Each discussion was taped, transcribed, and content-analyzed. Three distinct themes emerged. First, many participants believed that taking ART was lifesaving but missed doses because they feared that taking them in public would reveal their HIV status. Second, as a result, participants often found it difficult to integrate their regimens into the most basic daily activities. Finally, participants stressed the importance of having open, ongoing dialogues about their treatment plans and privacy needs with a wide range of health care workers. Multidimensional, tailored interventions may help persons living with HIV overcome the stigma and other complex barriers they face in taking antiretroviral therapy.
61 citations (Crossref) [2023-10-31]
Keywords: Adult; Antiretroviral Therapy; Highly Active; Attitude to Health; Female; Focus Groups; HIV Infections; Human immunodeficiency virus infection; Humans; Male; Middle Aged; North Carolina; Patient Compliance; United States; adult; antiretrovirus agent; article; attitude to health; clinical article; dept.pch; female; health care personnel; highly active antiretroviral therapy; human; information processing; male; middle aged; patient compliance; patient counseling; privacy; psychological aspect; virus infection

Sexual activity, orgasm and tampon use are associated with a decreased risk for endometriosis. - Meaddough, Erika L; Olive, David L; Gallup, Peggy; Perlin, Michael; Kliman, Harvey J (Gynecologic and obstetric investigation, 2002)
OBJECTIVE: The purpose of the study was to determine if sexual behaviors, orgasm, tampon use, and douching during menstruation modify the risk of endometriosis., METHODS: A case-control study was conducted. Subjects (n = 2,012) consisted of members of the Endometriosis Association and friends not affiliated with the organization who completed mailed surveys. Data were analyzed using chi(2), Fisher's exact test, t test, and regression analyses., RESULTS: There was no difference between study groups concerning douching practices. However, cases were less likely than controls to report sometimes or often engaging in sexual behaviors during menstruation (p = 0.002, OR = 1.5), and sexual behaviors during menstruation that included orgasm (p = 0.001, OR = 1.5). Cases were also less likely than controls to report using only tampons (p < 0.0001, OR = 2.6)., CONCLUSION: Sexual activity, orgasm, and tampon use during menstruation may confer protection against endometriosis. Copyright 2002 S. Karger AG, Basel
10 citations (Crossref) [2023-10-31] Place: Switzerland Meaddough, Erika L. Department of Public Health, Southern Connecticut State University, New Haven, CT, USA. Comment in (CIN)
Keywords: *Endometriosis/et [Etiology]; *Menstrual Hygiene Products/sn [Statistics & Numerical Data]; *Menstruation; *Orgasm; *Sexual Behavior; Adult; Case-Control Studies; Endometriosis; Female; Humans; Irrigation; Menstrual Hygiene Products; Menstruation; Orgasm; Orgasm/ph [Physiology]; Retrospective Studies; Sexual Behavior; Tampons; Therapeutic Irrigation; adult; article; controlled study; data analysis; dept.pch; endometriosis; female; human; hygiene; major clinical study; menstruation; orgasm; priority journal; regression analysis; sexual behavior; tampon